(3JfejI GdefGWb GdMVQjI GdeJOghQI GdBgdI HGdScGf HGdeTGQcI (B/ s - (3QjgGe eMeO ceGd eQGO LhOgs; (3QhjOg QVG cGed (B: s; (3eMeO eMeO GdHQedLi (B: s; (3egG SGei cGed (B: s ((3GdbGgQI (B: s (3QjgGe eMeO ceGd eQGO LhOg (B: s, 2013)
(3jJfGhd GdHMK bVjI GdefGWb GdMVQjI GdeJOghQI GdBgdI HGdScGf h YedjGJ GdJWhjQ h GdJfejI GdJi JJe HgG ef NdGd eHOC GdeTGQcI(B: (3h Pdc HgOa GdhUhd deDTQGJ(B/ (3eYGjjQ jecf UjGZJgG ai Tcd efgL EQTGOi jVe eLehYI eJJGHYI ef GdeQGMd jJe ef NdGdgG GdJYGed eY Jdc GdefGWb HTcd jVef JMbjb CaVd fJGFL eY ESJOGeI ecJSHGJ YedjGJ GdJfejI GdefaPI HgG(B: (3h Ydi gPG jbSe Edi OQGSI fXQjI deLehYI GdJYGQja h GdeaGgje hKjbI GdUdI HehVhY GdHMK HGdEVGaI deLehYI GdJLGQH GdYGdejI GdJi GYJeOJ Ydi GdeTGQcI GdeLJeYjI HYedjGJ GdJfejI h jdjgG GdOQGSI GdJWHjbjI Ydi GdMGdI GdeUQjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CSGdjH GdJONds; (3GdYThGFjGJs; (3GdefGWb GdScfjI GdeJOghQIs